A Phylogenetic Analysis of the Dirt Ants, Basiceros (Formicidae: Myrmicinae): Inferring Life Histories Through Morphological Convergence. Issue 4 (9th August 2019) - Probst, Rodolfo S; Wray, Brian D; Moreau, Corrie S; Brandão, Carlos R F
Abstract: Ants of the genus Basiceros Schulz, 1906 are elusive species known only from Neotropical rainforests. Little information is available regarding their natural history, and nothing is known about the phylogenetic relationships among species within the genus. The genus has been the subject of some controversy regarding generic delimitation but is currently a member of the ' Basiceros -genus group' following recent classification changes. For mouthparts, labral and mandibular morphologies present considerable variation in the Basiceros -genus group, likely a result of adaptive evolution. In Basiceros, those differences can be observed in the labrum shape and the various degrees of development of the labral cleft and the clypeomandibular space. Here, in an attempt to illuminate the evolution of the group, species boundaries are tested for Basiceros . The evolutionary relationships of its species are investigated using molecular and morphological data. Bayesian inference and maximum likelihood analyses of a molecular dataset consisting of up to nine genes (three mitochondrial, six nuclear) and including samples from multiple populations of all known Basiceros taxa recovered the monophyly of the genus and of its species, with two well-resolved internal clades: the singularis clade and the disciger clade. Focusing on the female castes of Basiceros, an ancestral state reconstruction is presented for mandibles and labrum morphology. The results suggest that the labrum and clypeomandibular morphologies are highly labile, although phylogenetically important characters in the genus. Mouthpart traits indicate a strong correlated evolutionary history potentially associated with specialized feeding habits.